Evaluation of intramedullary nailing in low-velocity gunshot wounds of the radius and ulna - Gelbart, Bradley Rael (My University, 2010)
Intramedullary nail insertion into a fractured bone allows stabilisation of the fracture with minimal intervention through the zone of injured tissue. This study aimed to assess whether intramedullary nailing of the forearm bones (radius and/or ulna) is a safe and effective form of management of these often complex fractures. A prospective case series was followed from presentation to fracture union. Between April 2006 and February 2008, 21 patients were enrolled in the study. The fracture union rate was high and complication rate was low. There was no increased risk of sepsis. The use of intramedullary nailing for diaphyseal fractures was successful but metaphyseal fractures, particularly with shortening, may be problematic. The use of intramedullary nailing for radius/ulna fractures is safe and effective, however the widespread use of this technique may be limited by the cost of the implant.
MMed (Orthopaedic Surgery), Faculty of Health Sciences, University of the Witwatersrand
Keywords: fracture fixation; nailing; radius; ulna